2010
DOI: 10.1111/j.1553-2712.2009.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Caffeine Ingestion Reduces Adenosine Efficacy in the Treatment of Paroxysmal Supraventricular Tachycardia

Abstract: Objectives: Caffeine, an adenosine receptor blocker, should theoretically reduce adenosine efficacy in the treatment of paroxysmal supraventricular tachycardia (SVT). We aimed to determine the effect of recent caffeine ingestion on the likelihood of reversion of SVT with adenosine.Methods: This was a multicenter, case-control study of adult patients with SVT treated with adenosine between September 2007 and July 2008. The primary endpoint was reversion to sinus rhythm (SR) after a 6-mg adenosine bolus, as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Therefore, pharmacokinetic and pharmacodynamic (PK/PD) interactions between caffeine and adenosine receptor ligands may contribute to the varying responses to an adenosine receptor-based drug in clinical trials (BOX 2). Indeed, PK/PD analyses show that recent caffeine ingestion (equivalent to two to four cups of coffee) affects A 2A receptor agonist-induced myocardial perfusion imaging 229 and reduces the efficacy of adenosine in the treatment of paroxysmal supraventricular tachycardia 230 . In this regard, it is somewhat surprising that several current clinical trials of adenosine receptor antagonists have not taken caffeine consumption into consideration in their clinical trial designs.…”
Section: Overview Of Adenosine Receptorsmentioning
confidence: 99%
“…Therefore, pharmacokinetic and pharmacodynamic (PK/PD) interactions between caffeine and adenosine receptor ligands may contribute to the varying responses to an adenosine receptor-based drug in clinical trials (BOX 2). Indeed, PK/PD analyses show that recent caffeine ingestion (equivalent to two to four cups of coffee) affects A 2A receptor agonist-induced myocardial perfusion imaging 229 and reduces the efficacy of adenosine in the treatment of paroxysmal supraventricular tachycardia 230 . In this regard, it is somewhat surprising that several current clinical trials of adenosine receptor antagonists have not taken caffeine consumption into consideration in their clinical trial designs.…”
Section: Overview Of Adenosine Receptorsmentioning
confidence: 99%
“…Dipyridamole, which inhibits the uptake of adenosine and thereby increasing its extracellular levels, was found to reduce the amount of adenosine required for the termination of PSVT involving the AV node [667]. In contrast, it has been suggested that caffeine (a non-selective adenosine receptor antagonist) ingestion reduces adenosine efficacy in the treatment of PSVT [668], although, the methodology of the latter study was subsequently criticised [669].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…We thank Drs. Karydes and Bryant for their comments on our article 1 and agree that our study design had flaws that limit the strength of the conclusions. These limitations are well described in the article.…”
mentioning
confidence: 74%